2020
DOI: 10.1371/journal.pone.0240349
|View full text |Cite
|
Sign up to set email alerts
|

A daily diary study on adolescents’ mood, empathy, and prosocial behavior during the COVID-19 pandemic

Abstract: Adolescence is a formative phase for social development. The COVID-19 pandemic and associated regulations have led to many changes in adolescents' lives, including limited opportunities for social interactions. The current exploratory study investigated the effect of the first weeks of COVID-19 pandemic lockdown on Dutch adolescents' (N = 53 with attrition, N = 36 without attrition) mood, empathy, and prosocial behavior. Longitudinal analyses comparing pre-pandemic measures to a three-week peri-pandemic daily … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
115
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 44 publications
10
115
3
5
Order By: Relevance
“…These results are consistent with available international literature 12,14 and those from the same geographical region as our study 43 . Similarly, as demonstrated by previous research 27,44 , the high objective risk group also consisted of people with more empathic concern compared to the other groups. Finally, even though the risk situation was significantly associated with the acceptance of the lockdown (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are consistent with available international literature 12,14 and those from the same geographical region as our study 43 . Similarly, as demonstrated by previous research 27,44 , the high objective risk group also consisted of people with more empathic concern compared to the other groups. Finally, even though the risk situation was significantly associated with the acceptance of the lockdown (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Other research conducted during the COVID-19 outbreak indicates, however, that empathy levels might fluctuate according to anxiety linked to risk exposure/perception and modulate prosocial willingness [26][27][28] . Perceived risk may be relative to the individual (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Our main finding of stable mood levels during the first few months of the COVID-19 pandemic in early adolescents aged 9–12 years was in contrast with our expectation of decreased mood variability with the easement of social containment measures. Interestingly, previous studies on mood levels during the first few months of the COVID-19 pandemic are mixed as studies showed both an increase in negative mood (Li et al, 2020 ; Orgilés et al, 2020 ; Whittle et al, 2020 ; De Quervain et al, 2020 ; Barendse et al, 2021 ; Luijten et al, 2021 ) as well as a stable or decrease in negative mood (Van De Groep et al, 2020 ; Achterberg et al, 2021 ; Fried et al, 2021 ) in children, adolescents, and college students. These seemingly discrepant findings might be explained by methodological differences, such as parent vs. child report.…”
Section: Discussionmentioning
confidence: 99%
“…Through social involvement, the mood changes (from negative to positive, or from positive to even more positive) and thus well-being is enhanced. Living empathically leads to opportunities for social involvement and prosocial behaviour, which can be constituted as an important predictor for developing socio-emotional health (Van de Groep et al, 2020). To empathically resonate is a way to experiment to what someone other expresses, to understand on a significance level what the other is trying to express.…”
Section: Resultsmentioning
confidence: 99%